Cardiac failure detection in 30 minutes: new approach based on gold nanoparticles. (17th February 2017) - Namdari, Mehrdad; Negahdari, Babak; Cheraghi, Mostafa; Aiyelabegan, Hammed T.; Eatmadi, Ali
Abstract: Cardiac failure occurs when heart is unable to pump sufficiently to maintain blood flow to meet the body's needs. The aim of this work is to detect highly expressed genes: follistatin-related protein 1 (FSTL1) in heart failure within 30 minutes, using gold nanoparticles. Gold nanoparticles were prepared by citrate reduction of HAuCl4 3H2 O; probe sequence was designed based on the FSTL1 gene region. Preparation of gold nanoprobes (AuNPs) proceeded by treating all the containers with DEPC-treated water, followed by reduction and conjugation. Transmission electron microscopy shows that AuNPs were 10–15 nm in size. The concentration of the nanoprobes was 2.1 nM, and they bind to target. Real-time PCR shows an over-expression of FSTL1 and FSTL3 in heart failure ( p  < .05). Our data showed that elevated expression of the FSTL1 and FSTL3 is a marker of heart failure as detected within 30 minutes by the synthesised AuNPs; the method is accurate and fast.